High-Throughput primary Screenings of catalysts for catalytic combustion of waste flue gas from pyrolysis process using a multi-flow reactor - Vachanee Teachasiri (Chulalongkorn University, 2014)
Thesis (M.Sc.) -- Chulalongkorn University, 2006